PENGARUH KOMPOSISI SERAT KENAF DAN SERBUK CACO3 TERHADAP KEKUATAN TEKUK DAN WATER ABSORPTION KOMPOSIT HYBRID-POLIESTER - Alfian Hudan Laksana; Marhadi Budi Waluyo (Politeknik Negeri Ketapang, 2021)
The reinforcing composition in hybrid composite can affect the material properties. Kenaf fiber (Hibiscus Cannabinus L.) can be used as a reinforcement for hybrid composites with high advantage. Calcium carbonate serves as a reinforcement for composite materials and was useful for increasing stiffness. The purpose of this study was to analyze the effect of variations in the composition of the addition of kenaf fiber and CaCO3 powder on the flexural strength and water absorption properties of the calcium carbonate reinforced kenaf fibers/polyester hybrid composites (PTJ/SK/CaCO3) made by hand layup method. Hybrid composites were made with various compositions of CaCO3 (0%, 2.5%, 5%, 10%, and 20% by weight). The results showed that the PTJ/SK/CaCO3 (5%wt) hybrid composite had the highest flexural strength with a value of 74.87 MPa. The increase in the amount of CaCO3 powder composition showed a decrease in the water absorption of the PTJ/SK/CaCO3 hybrid composite.